2002
DOI: 10.1081/jdi-120002655
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Fat Elimination Between Long-Chain Triglycerides and Medium-Chain Triglycerides in Rats With Ischemic Acute Renal Failure

Abstract: To guide the administration of fat emulsion in the nutritional support of acute renal failure (ARF), pharmacokinetic analysis with an one-compartment open model after bolus intravenous injection was performed to compare the elimination kinetics of long-chain triglycerides (LCT) and medium-chain triglycerides (MCT) in ischemic acute renal failure rats. Sprague-Dawley rats were randomized into four groups, namely LCT normal group, LCT ARF group, MCT normal group and MCT ARF group. The model of ischemic acute ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Triglycerides are hydrolysed to release fatty acids, and the rate of metabolism of free fatty acids is very much dependent upon the carbon chain length. Ge et al [26] demonstrated that the maximal reactive rate of lipoprotein lipase hydrolysis on MCT was 2.2 times faster than on long chain triglycerides (LCT), and the reactive rate for the hydrolysis of hepatic triglycerides lipase on MCT was 1.2 times faster compared to LCTs. Given that MCFA have a shorter chain length, they are delivered directly to the liver via the hepatic portal vein to undergo the β-oxidation process [13].…”
Section: Discussionmentioning
confidence: 99%
“…Triglycerides are hydrolysed to release fatty acids, and the rate of metabolism of free fatty acids is very much dependent upon the carbon chain length. Ge et al [26] demonstrated that the maximal reactive rate of lipoprotein lipase hydrolysis on MCT was 2.2 times faster than on long chain triglycerides (LCT), and the reactive rate for the hydrolysis of hepatic triglycerides lipase on MCT was 1.2 times faster compared to LCTs. Given that MCFA have a shorter chain length, they are delivered directly to the liver via the hepatic portal vein to undergo the β-oxidation process [13].…”
Section: Discussionmentioning
confidence: 99%
“…One of them is the unknown plasma level of LE or the LA, although the administration was according to international guidelines for lipid rescue in LAST. However, the time interval between LE and LA administration in our setup (2 min) was much shorter than the half-life of long-chain triglycerides, the main constituent of Intralipid administered in rats, which was reported to be more than 30 min [ 22 ]. We can thus safely assume that most of the LE was still present in the circulation at the time Ropivacaine was injected.…”
Section: Discussionmentioning
confidence: 99%